Notes on Aphodius coenobita Gravenhorst, 1807, a forgotten name (Coleoptera: Scarabaeidae: Aphodiinae) - Fery, Hans; Dellacasa, Giovanni; Dellacasa, Marco (Zootaxa, 2021)
Aphodius coenobita Gravenhorst, 1807 is an almost forgotten name which has never been used as valid after its establishment. Studies of Gravenhorst’s life story and his relations with contemporary entomologists revealed that at least a part of the original syntype series of this taxon is stored in the “Museum für Naturkunde Berlin” (Germany). Furthermore, it is given evidence that Aphodius stercorosus F.E. Melsheimer, 1844 (currently placed in the genus Blackburneus Schmidt, 1913) is a junior synonym of Gravenhorst’s name. In order to stabilise the nomenclature the name A. coenobita is declared to be a nomen oblitum under Article 23.9 of the Code of Zoological Nomenclature. At the same time A. stercorosus is declared a nomen protectum and it is given precedence over the older name. Additionally, one and the same specimen of the syntype series is designated as lectotype for both taxa.